Development of mobile web based online catering booking system for One Stop Center / Anis Athirah Lukman - Lukman, Anis Athirah (2017)
This project was develop to enhance the existing system for the company One Stop Centre which the shop named Ilham Katering that located in Batu Berendam, Melaka. The problem arises regarding to the company that still using manual system for booking and mess up in handling booking forms from customers. The system was developed for the customer to having a medium for online booking which help the customer to get suitable package for the event. There are three objectives generated for this project - to gather and analyse the requirements of Catering Booking System (CBS), to design a website of CBS, to develop full working mobile web based of CBS. This project was developed using three phases in Rapid Application Methodology which are Requirement/ Planning, User Design and Construction phase. The mobile web based was establish within the consideration for organizations seek as the mobile use continues to grow worldwide. Mobile web based is similar to other website which consists of HTML pages that design for smaller handheld display and touch screen interface that are linked together and access over the internet such as WiFi or 3G or 4G networks. The responsive web design need to become a new standard website which is mobile-friendly that can scale to any size of device. For the result of this project, developer make a system where customer can view the recommendation package that suggested by the system, the customers are required to enter the estimate guest and estimate budget for the event. For future recommendation, the system need to add the payment method for customer to make transaction via online banking or any other payment method. Besides that, the customer‟s email validation need to implement into the system to ease the confirmation or notification for customer.